2011
DOI: 10.1371/journal.pone.0029101
|View full text |Cite
|
Sign up to set email alerts
|

Quantification Bias Caused by Plasmid DNA Conformation in Quantitative Real-Time PCR Assay

Abstract: Quantitative real-time PCR (qPCR) is the gold standard for the quantification of specific nucleic acid sequences. However, a serious concern has been revealed in a recent report: supercoiled plasmid standards cause significant over-estimation in qPCR quantification. In this study, we investigated the effect of plasmid DNA conformation on the quantification of DNA and the efficiency of qPCR. Our results suggest that plasmid DNA conformation has significant impact on the accuracy of absolute quantification by qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 18 publications
3
53
0
Order By: Relevance
“…Lin et al [8] reported a similar finding, with a 3-fold increase in the NK603/ zSSIIb gene(s) using the eukaryotic system, maize. Interestingly, little attention has been paid to the effect of circular plasmid standards in bacterial and archaeal systems which commonly have genomes and plasmids that are circular, although linear forms are found in some cases [9].…”
Section: Introductionmentioning
confidence: 59%
“…Lin et al [8] reported a similar finding, with a 3-fold increase in the NK603/ zSSIIb gene(s) using the eukaryotic system, maize. Interestingly, little attention has been paid to the effect of circular plasmid standards in bacterial and archaeal systems which commonly have genomes and plasmids that are circular, although linear forms are found in some cases [9].…”
Section: Introductionmentioning
confidence: 59%
“…By contrast, the analytical sensitivity using samples with intact B. microti parasites in infected RBCs was 2.7 parasites/l, which was ∼7-fold less sensitive than that established using samples spiked with plasmid DNA. Both reductions in DNA extraction efficiency and reduced PCR amplification have been well documented using intact organisms containing large genomic DNAs versus extracellular, small plasmid DNA fragments (Lin et al, 2011;Yun et al, 2006). Imprecision in the measurement of parasitemia in a patient sample and in the estimation of the plasmid copy numbers in DNA used for the spiking may also contribute to the observed difference (College of American Pathologist, 2013;Applied Biosystems, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, the analytical sensitivity of real-time PCR assays was most often assessed by spiking plasmid DNA to negative blood samples, which may result in inaccurate results due to the potential for preferred amplification by PCR of small plasmid DNA fragments, compared with the same target sequence contained within the complete genome of a microorganism (Lin et al, 2011;Yun et al, 2006). Moreover, there are only very limited data available on the performance of real-time PCR for diagnosis and monitoring of treatment in patients with babesiosis in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Slight imprecision in measurements of the concentration of the plasmid DNA used in the preparation of the external standard could adversely affect the accuracy of estimates of the target DNA in patient samples, since just 1 ng of the plasmid DNA (3080 bp) is equivalent to 3.01 × 10 8 copies of target DNA. In addition, it is possible that the complexity of B. microti genomic DNA (~6.5 Mbp) in patient samples, compared with that of the cloned plasma DNA (3080 bp) used as the external standard, led to an underestimation of the quantity of the target DNA in the patient samples (Lin et al, 2011). Other factors that might have contributed to a reduction in the estimated quantity of the Babesia DNA target in blood include incomplete lysis of erythrocytes and/or of the parasite itself or inefficient PCR amplification; however, none of these would have been anticipated since the standard DNA extraction protocol used in this study lyses leukocytes well (Qiagen, 2012), and the PCR was found to be highly efficient with a calculated efficiency of~95% (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%